Literatur Review : Pengaruh Pembelajaran Flipped Classroom di Abad 21 terhadap Kemandirian Belajar Pesera Didik - Outhariy, Ailsa Nadia; Nabilla, Nayla; Rahmawati, Tasya; Rimba, Rts Mustika; Sitohang, Natalia; Siburian, Jodion; Mardiyanti, Lely; Astriawati, Fitri (Unversitas Muhammadiyah Mataram, 2025)
Independent learning is a key 21st-century competency that students still lack, requiring innovative learning strategies. The implementation of the flipped classroom is believed to increase students' independent learning. This study aims to analyze the effect of the flipped classroom learning model on independent learning in the 21st century. This study is a literature review that relies on sources published between 2020 and 2025, all of which are academic journals. All articles listed have been accredited to a minimum standard of SINTA 5. The literature search was conducted through Google Scholar by typing the keywords “flipped classroom” and “learning independence.” The articles obtained were analyzed in depth and the results were described using tabulation. From the results of the literature analysis, it was concluded that the Flipped Classroom has an effect on student learning independence and can improve student learning outcomes.